Meningkatkan Kesadaran Masyarakat Terhadap Lingkungan Melalui Kegiatan Trash Festival And Art Exhibition - Arfa, Muhammad; Haryono, Haryono; Hairani, Hairani; Fatimatuzzahra, Fatimatuzzahra; Madani, Miftahul; lnnuddin, Muhammad (ADMA : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2023)
The purpose of this research is to respond to the impact of waste on the environment through art festivals and exhibitions, workshops, music festivals and photography competitions. The results of the activity were very effective in inviting all parties to jointly protect the environment from waste and increasing public awareness to dispose of waste in its place, collaboration between the government and the Zero Waste program and several waste bank communities and the VIBE community. very effective every year as a form of shared responsibility to reduce waste accumulation in West Nusa Tenggara.